The Untranslatability of Shakespeare’s Poetry on Love - Acim, Rachid (Vertimo studijos, 2017)
[full article and abstract in Lithuanian; abstract in English]Translating Shakespeare’s poetry has been one of the most arduous questions that has pained many translators, researchers and academics worldwide. As this poetry involves many rhetorical devices, alternating between the use of keen imagery and intertextuality, it not only lends itself to ambiguity but also to untranslatability; moreover, the use of figures of speech such as similes, synecdoche and metaphors accord this poetry a discursive power that does not recede despite the evolution of the English language and the death of the poet many centuries ago. And while this poetry addresses a whole galaxy of themes, it projects Shakespeare himself as a cosmopolitan figure not limited to time or even space. The present study seeks to assess and evaluate the translation solutions given as concerns Shakespeare’s poetry on the theme of “love”. To achieve this aim, I suggest employing a contrastive analysis between the English and Arabic poetic text, with a view to exploring whether or not the core of this poetry has been preserved. My assumption is that the stylistic aspects and aesthetic properties of the original poetic text are lost due to the intentional or unintentional intervention of the translator.
Keywords: none